Routinized Syphilis Screening Among Men Living With Human Immunodeficiency Virus: A Stepped Wedge Cluster Randomized Controlled Trial. (27th June 2021) - Burchell, Ann N; Tan, Darrell H S; Grewal, Ramandip; MacPherson, Paul A; Walmsley, Sharon; Rachlis, Anita; Andany, Nisha; Mishra, Sharmistha; Gardner, Sandra L; Raboud, Janet; Fisman, David; Cooper, Curtis; et al.
Abstract: Background: We implemented an opt-out clinic-based intervention pairing syphilis tests with routine human immunodeficiency virus (HIV) viral load testing. The primary objective was to determine the degree to which this intervention increased the detection of early syphilis. Methods: The Enhanced Syphilis Screening Among HIV-Positive Men (ESSAHM) Trial was a stepped wedge cluster-randomized controlled trial involving 4 urban HIV clinics in Ontario, Canada, from 2015 to 2017. The population was HIV-positive adult males. The intervention was standing orders for syphilis serological testing with viral loads, and control was usual practice. We obtained test results via linkage with the centralized provincial laboratory and defined cases using a standardized clinical worksheet and medical record review. We employed a generalized linear mixed model with a logit link to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of the intervention. Results: A total of 3895 men were followed over 7471 person-years. The mean number of syphilis tests increased from 0.53 to 2.02 tests per person per year. There were 217 new diagnoses of syphilis (control, 81; intervention, 136), for which 147 (68%) were cases of early syphilis (control, 61 [75%]; intervention, 86 [63%]). The annualized proportion with newly detected early syphilis increased from 0.009 to 0.032 with implementation of the intervention; the corresponding time-adjusted OR was 1.25 (95% CI, .71–2.20). Conclusions: The implementation of standing orders for syphilis testing with HIV viral loads was feasible and increased testing, yet produced less-than-expected increases in case detection compared to past uncontrolled pre–post trials. Clinical Trials Registration: NCT02019043. Abstract : In a randomized, multisite trial that implemented standing orders for syphilis serological testing with HIV viral loads among men, we observed significant increases in syphilis testing and a 25% increase in detection of new cases of early infectious syphilis.